2016
DOI: 10.1038/bjc.2016.98
|View full text |Cite
|
Sign up to set email alerts
|

Association between dietary inflammatory potential and breast cancer incidence and death: results from the Women’s Health Initiative

Abstract: Background:Diet modulates inflammation and inflammatory markers have been associated with cancer outcomes. In the Women's Health Initiative, we investigated associations between a dietary inflammatory index (DII) and invasive breast cancer incidence and death.Methods:The DII was calculated from a baseline food frequency questionnaire in 122 788 postmenopausal women, enrolled from 1993 to 1998 with no prior cancer, and followed until 29 August 2014. With median follow-up of 16.02 years, there were 7495 breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
2
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 91 publications
(97 citation statements)
references
References 55 publications
2
90
2
3
Order By: Relevance
“…Among the 7 studies included, 1 population-based casecontrol study was conducted in Germany (26); 3 prospective cohort studies were conducted in the United States [Nurses' Health Study (NHS) (14,15) and Women's Health Initiative cohort study (21)]; and the other 3 were conducted in European countries [European Prospective Investigation into Cancer and Nutrition Cohort (EPIC) study (27), Swedish Women's Lifestyle and Health cohort study (28), and Netherlands cohort study (29) Duplicates removed (n = 50) FIGURE 1 Literature search flow chart.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the 7 studies included, 1 population-based casecontrol study was conducted in Germany (26); 3 prospective cohort studies were conducted in the United States [Nurses' Health Study (NHS) (14,15) and Women's Health Initiative cohort study (21)]; and the other 3 were conducted in European countries [European Prospective Investigation into Cancer and Nutrition Cohort (EPIC) study (27), Swedish Women's Lifestyle and Health cohort study (28), and Netherlands cohort study (29) Duplicates removed (n = 50) FIGURE 1 Literature search flow chart.…”
Section: Resultsmentioning
confidence: 99%
“…In the population-based case-control study of postmenopausal breast cancer in Germany, 428 ER−/progesterone receptor-negative (PR−) cases from the MARIE (Mammary Carcinoma Risk factor Investigation) study showed no association between the DII and risk of the ER−/PR− breast cancer (OR comparing the top to bottom quintiles of the DII: 0.87; 95% CI: 0.63, 1.20; P-trend = 0.24) (26). In the United States, the Women's Health Initiative observational study followed 70,998 women for a median of 16 y, with a total of 381 ER−/PR− cases (21). Analysis was completed separately by human epidermal growth factor 2 status, and a higher DII was associated with a higher risk (30).…”
Section: Dietary Inflammatory Index the Dietary Inflammatorymentioning
confidence: 99%
See 2 more Smart Citations
“…[31] A meta-analysis of adult dietary patterns derived using PCA/factor analysis has suggested an 7% reduced risk of breast cancer for women in the highest category of adult prudent/healthy dietary pattern score (95% CI, 0.88 to 0.98). [7] Among the three study populations that have examined adult dietary inflammation potential and breast cancer outcomes, two reported no significant association with overall breast cancer risk[3234] and one reported a borderline positive association between DII and breast cancer. [35] To our knowledge, the NHS II cohort is the only study to examine adolescent dietary patterns derived by PCA while no studies have examined an adolescent diet DII and breast cancer risk.…”
Section: Discussionmentioning
confidence: 99%